74.9k views
4 votes
What is the inverse of the function f(x) = 2x– 12?

h(x) = 48x - 4
h(x) = 48x + 4
h(x) = 4x - 48
h(x) = 4x + 48

User Isca
by
4.9k points

1 Answer

7 votes

Answer:

Explanation

For the time, call f(x) = y

Interchange x and y

y = 2x - 12

x = 2y - 12

Add 12 to both sides

x + 12 = 2y

Divide both sides by 2

x/2 + 12/2 = y

x/2 + 6 = y

x/2 + 6 = h(x)

Nothing I'm getting looks like what you've given us. Perhaps this is a different question?

User Tonianne
by
4.9k points